Increasing the Activeness and Interest in Reading the People of Kampung Anyar Through the Kauri Reading Corner - Fadhli Rusydi; Khoirunisa Khoirunisa; Della Rahmaniah; Afdal Alif; Ahmad Baihaky (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Real work lectures (KKN) are examples of student service to the community. KKN students must be involved in educational activities if they want to improve the lives of the nation. Thus, counseling activities are carried out to help KKN students create community service programs in educational aspects. Group 1 of UNUSIA 2023 KKN carried out this activity. This activity can be carried out well and produce KKN student activity programs in the field of education, such as building a reading corner. The community of Kp. Anyar Desa Tegal is the target of this activity.